Mobile volunteer and event coordination and management system - Wong, Wai Kiat (2024)
A Mobile Volunteer and Event Coordination and Management System is a digital platform that connects volunteers with voluntary activities and opportunities that match their skills. In today’s rapidly evolving world, volunteerism has become an essential force for positive change. With a growing number of volunteers and a diverse range of voluntary activities, efficiently managing this vital resource has become increasingly complex. In response to these issues, this is a project to develop a mobile volunteer and event coordination and management system. The proposed project is able to match volunteers’ skills with a similarity score that considers the user’s skills and distance of the user. Besides, by integrating the map function, it can enhance the volunteer experience by easily searching for nearby voluntary activities, eliminating the need to manually enter the address. Moreover, to keep users informed, notifications and updates will be regularly sent out, ensuring volunteers stay connected to the latest opportunities.